Compliance with Standard Precautions and Associated Factors Among Health Professionals in Public Hospitals of East Wallaga Zone, Oromia Regional State, Ethiopia - Feyisa BR; Demisie W; Tesfaye E (Dove Medical Press, 2022)
Bikila Regassa Feyisa,1,2 Wubitu Demisie,3 Edosa Tesfaye1 1Department of Public Health, Institute of Health Sciences, Wallaga University, Nekemte, Ethiopia; 2Department of Epidemiology, Faculty of Public Health, Jimma University, Jimma, Ethiopia; 3Nekemte Specialized Hospital, Oromia, EthiopiaCorrespondence: Bikila Regassa Feyisa, Department of Epidemiology, Faculty of Public Health, Jimma University, Jimma, P.O. Box 378, Ethiopia, Tel +251927488235, Email bikregasa@gmail.comPurpose: Health care workers are potentially exposed to infections through contact with blood and bodily fluids while performing their duties. Compliance with the standard precautions reduces the risks of health care workers' exposure to blood and bodily fluids. However, the compliance level among health care workers is not well studied in the study area. Therefore, this study aimed to assess the level of compliance with standard precautions and its associated factors among health care workers in all public hospitals of East Wallaga Zone, Western Ethiopia.Materials and Methods: Multi-facility-based cross-sectional study was conducted among 392 health care workers, from January to February, 2022. Simple random sampling technique was used to select study participants. Logistic regression model was fitted to determine presence of statistically significant associations. A p-value of less than or equal to 0.05 along with the adjusted odds ratio of 95% confidence interval was used to declare statistical significance.Results: The proportion of health care workers who comply with standard precautions was found to be 51.6% [95% CI; 46.9- 56.7%]. Having positive attitude towards standard precautions (AOR=2.71; 95% C.I: 1.68- 4.39), having training on standard precautions (AOR=3.27; 95% C.I: 2.019- 5.29), and working in referral hospitals (AOR=1.83; 95% C.I: 1.13- 2.96) were the associated factors of good compliance with standard precautions.Conclusion: In this study, half of the health care workers comply with standard precautions. Positive attitude, training, and level of hospitals were factors for compliance with the standard precautions. As a result, to sustain and improve compliance of health care workers on standard precautions, periodic in-service training is needed to bring about behavioral changes among health care workers, particularly for those working in other settings than referral hospitals.Keywords: compliance, standard precautions, health care workers, public hospitals, Ethiopia